THE IMPORTANCE OF THE GYROSCOPE SENSOR IN THE DEVICES, ESPECIALLY IN THE PLANE - Khaleel Ali Khudhur (Journal of Artificial Intelligence and Digital Economy, 2026)
Objective: The secret to producing high-precision tension for connection with a proposed gyroscope (CMGs) in spaceships is the fast speed regulation of gyroscope servo systems. Nevertheless, disturbances, particularly dynamic balancing disturbances that have the exact wavelength as the high-speed rotor, may severely reduce the system stability of gimbal robotic manipulators. Using a dynamic balanced machine to number of key factors the rotor imbalance in built CMGs is quite challenging. In order to calculate the dynamic instability of the rotor built in the CMG, a gimbal disturbances investigator is proposed in this study. Method: First, a third-order nonlinear system is created to characterize the behaviors of the disturbances in the gimbal servo system. In this system, the other problems and the rotational dynamic balancing torque along the gimbal axis are treated as being periodic and bounded, respectively. Using the complete disruption as a virtual observation, the gimbal disturbances observer is then created for the second dynamical system. Since the simulated measure is produced from the inverse kinematics of the stabilizer servo system, only observations of gimbal rotation and three-phase flux may be used to indirectly determine the knowledge of the rotating dynamic imbalance. Results: Results from semi-physical experiments show how well the observer works when a CMG simulator is used. Novelty: In order to calculate the dynamic instability of the rotor built in the CMG, a gimbal disturbances investigator is proposed in this study.